PWE-096 What is the cost of delayed diagnosis of bile acid malabsorption?. (8th June 2018) - Fernandes, Darren; Poon, Dennis; White, Laura; Andreyev, Jervoise
Abstract : Introduction: Bile acid malabsorption (BAM) is accurately diagnosed using a 75 selenium taurocholic acid (SeHCAT) scan which also defines treatments patients require. BAM causes chronic, often debilitating symptoms including loose stool, faecal incontinence and abdominal pain. Primary BAM affects 1% of Britons yet is frequently misdiagnosed as IBS. A further 1% have BAM secondary to other conditions. The 2012 NICE DG7 review of SeHCAT included a cost-effectiveness evaluation based on assumptions without supporting evidence. Our aim was to evaluate the cost of delayed diagnosis of BAM. Methods: The notes of all patients undergoing SeHCAT scanning in our Trust over a one-year period were reviewed retrospectively. The number of abnormal scans and patient response to treatment were recorded. Costs of additional clinics/tests/procedures performed before the diagnosis of BAM were calculated using NICE costing templates. Results: 1.5% of 3860 new patients seen in our gastroenterology clinics between June 2016-May 2017, 19 men and 37 women, median age 58 (range 19–83) were referred for SeHCAT scanning. Of these, 64% were abnormal: 13 demonstrated severe (<5% 7 day SeHCAT retention), 13 moderate (5%–10%), 5 mild (10%–15%) and 5 borderline (15%–20%) BAM. Underlying causes for BAM included cholecystectomy (n=13), chronic unexplained symptoms (n=12), inflammatory bowel disease (n=4), irritable bowel syndrome (n=4), right hemicolectomy for bowel cancer (n=1), diabetes mellitus (n=1) and multiple possible causes (n=1). If SeHCAT scanning was ordered at first consultation (n=11), patients reported 24 months (median) of symptoms (range 6–360) and the mean diagnostic package of care cost was £910.75. If the SeHCAT scan booked 2nd line or later (n=25), patients reported symptoms for 30 months (median, range 0.5–360) and mean diagnostic package of care cost was £1, 481.73. However, in these patients 9 additional abnormalities were found: vitamin D deficiency (n=3), diverticulosis (n=2), folate deficiency (n=1), oesophageal dysmotility (n=1), renal cell carcinoma requiring nephrectomy (n=1) and Helicobacter Pylori gastritis (n=1). Following diagnosis, treatment led to reported symptom improvement (n=24), no change/deterioration (n=3), not reported (n=9). Conclusions: In our Trust, SeHCAT scanning is enormously underused. Late diagnosis of BAM is associated with markedly increased costs, unnecessary demands for other services and treatment delay for patients. National data on SeHCAT usage suggest that our findings will apply to most other Trusts. More emphasis to ensure early diagnosis of BAM, a frequent, unpleasant and treatable condition would bring the unusual but highly desirable result of significant health benefits while substantially reducing healthcare costs.